Diachronic study (survey) of terminological units related to hydrotechnical construction in Uzbek, Russian and English languages - Babakulova Luiza Ravshanovna (Zien Journals, 2022)
The beginning of any new sphere leads to the creation of a certain terminological system, and the development of this industry over the centuries leads to the development of a terminological system.
Keywords: terminology; hydrotechnic; hydrotechnical construction; ditch